Efficient decontamination of RO concentrate in a sonochemical zero-valent iron/persulfate Fenton-like system: The molecule-size preferred degradation of dissolved organic matters. Issue 3 (June 2022) - Xiang, Wei; Zou, Xiaoli; Huang, Mingjie; Wu, Xiaohui; Zhou, Tao
Abstract: Interference of real dissolved organic matters (DOMs) in advanced oxidation processes (AOPs) treatment of pharmaceuticals in reverse osmosis concentrates (ROC) has rarely reported. In this study, an ultrasound/zero valent iron/persulfate (US/ZVI/PS) system has been developed to degrade typical antibiotic sulfadiazine in the presence of co-existing ROC DOMs. It was found that common inorganic anions slightly affected the removal of SD, while fulvic acid (FA) and humic acid (HA) would bring medium to strong inhibition. 3D-EEM results evidenced the degradation of DOMs attributed to their competition for the oxidative radicals, suggesting the selective attack liable to larger molecular sizes. Intensive hydroxylation of HA and cleavage of C-C in FA molecule would occur respectively, where benzene ring, carbonyl or conjugated carbonyl group in DOMs would be destructed with oxidation of the nitrogen-containing functional groups. Scaled-up dosages of the agents could achieve efficient decomposition of all the three DOMs in a SD-spiked pristine ROC and all macromolecular structures were transformed into small molecules, suggesting the US/ZVI/PS system would be an good option for treating practical ROCs. Graphical Abstract: ga1 Highlights: A sonochemical Fe 0 /persulfate system was developed to degrade sulfadiazine-spiked RO concentrate. Inorganic anions slightly affected SD removal, while fulvic acid and humic acid would bring medium to strong inhibitions. Selective radical attack on DOMs was observed selective depending on their molecular sizes. Intensive hydroxylation and C-C cleavage occurred on FA and HA molecules, respectively. Scaled-up agent dosages in the US/ZVI/PS system achieved efficient decontamination of RO concentrate.